Interseeding lespedeza into crabgrass pasture versus additional nitrogen fertilization on forage production and cattle performance - Lyle W. Lomas; Joseph L. Moyer; F.K. Brazle; Gary L. Kilgore (Kansas Agricultural Experiment Station Research Reports, 2003)
A total of 160 steers grazed "˜Red River' crabgrass pastures that were either fertilized with additional nitrogen (N) or interseeded with lespedeza during the summers of 1998, 1999, 2000, and 2001. Wheat was also grazed in 1999, 2000, and 2001 prior to crabgrass emergence. Legume cover, forage dry matter production, grazing steer performance, and subsequent feedlot performance were measured. Available forage dry matter and grazing steer performance were similar between pastures of crabgrass fertilized with additional N and those interseeded with lespedeza in 1998, 1999, and 2000. In 1999, finishing feed intake, finishing gain and ribeye area were higher (P0.05) between pastures fertilized with additional N and those interseeded with lespedeza. Therefore, economics rather than cattle performance would likely determine which option a producer might select. This study will be continued for three additional grazing seasons with no additional crabgrass being seeded to determine whether crabgrass will voluntarily re-seed itself sufficiently to sustain the system.
Keywords: Cattlemen' s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Interseeding lespedeza; Interseeded; Crabgrass pasture; Nitrogen fertilization; Forage production; Cattle performance